PEMANFAATAN CURL PADA PHP GUNA MENDAPATKAN INFORMASI MALWARE DENGAN MEMANFAATKAN AVG THREAD LABS - HENDRO PURWOKO (LPPM, 2016)
Malware has existed for more than 40 years, according to the report from Panda Security on it’s annual report, only within 3 months there’s been about 205.000 until 225.000 new variants. Malware does not only attack the PC (Personal Computer), but also a mobile phone which has an operating system. The enterance of malware into gadget is caused by users when doing activities such as social media, download, open email attachments or even when accidentally press the advertisement which containing malware. This study discusses about the process of making a web-based application which can be used to detect malware using CURL as a trigger in the process of scanning that can give orders to the AVG Theard Labs to check the URL. Keywords: malware, malware scanner, CURL, PHP, web